Pengaruh Literasi Digital Keuangan Terhadap Keputusan Generasi X dalam Menggunakan Aplikasi Perbankan (Jurnal Riset Manajemen dan Akuntansi, 2025)
This research aims to determine the influence of digital financial literacy on Generation X's decision to use banking applications. The approach used is quantitative with a correlational type of research. The sample consisted of 30 respondents aged 45–60 years who had used digital banking applications for at least the last three months. Data was collected through a questionnaire with a Likert scale and analyzed using validity, reliability, normality, Pearson correlation and simple linear regression tests. The results of the analysis show that there is a positive and significant relationship between financial digital literacy and the decision to use banking applications, with a correlation coefficient of 0.672 and a significance value of 0.000. The regression equation obtained is Y = 1.584 + 0.628X, with an R² value of 0.395. This means that 39.5% of the decision variables to use banking applications are influenced by financial digital literacy. This research concludes that increasing financial digital literacy can significantly improve Generation X's decisions in utilizing digital banking services.